Diasporic Pariah: A Study of Bessie Head’s Maru - Turki, Harith Ismael; Işık, Zeliha (Journal of History Culture and Art Research, 2021)
Home is a very important notion in human life which helps people establish emotional, social and intellectual belonging and identifications so that they can hold on to life. When the sense of home is contested, the sense of identity is impaired too. Those people who are characterized by the sense of disconnectedness and desire to re-establish their home are known as diasporic people. The protagonist of Maru (1971), Margaret is one of those diasporic people who long for home and attachments to people. This article is an attempt to examine the struggle of Margaret against a ruthless and cruel society. In her status as a diasporic individual, Margaret is seen as a nonhuman being due to her race, as a Masarwa, living in Botswana. She is alienated, and treated as a pariah, because she does not belong to a superior race defined by the colonial British forces which ruled Botswana. The article tries to view the protagonist’s estrangement and her experience as a diasporic pariah through the lenses of some of the famous postcolonial critics and writers. It also tries to explore the origins and aspects of this kind of treatment.